A metáfora viva em Quintana - Silva, Nilda Maria da Rocha (2009)
This dissertation has as base of study full Mario Quintana book, it has a propose of to study the metaphoric language and to show also traces of Surrealism which can be seen in different texts. In it will be showed that Quintana has a lyric poetry enjoyed strong irony and single authenticity. Mario build a poetry speech without artificialism. Modern writer, he mode everything to tell of his of his desire of being free of the literary label, he didn t become attached to follow any manner and didn t want to be put in poetry style. The surrealists traces of his poet has a faze paper which put him like a absolute creator. This attitude is more than a way of expression, it is an antidote to the common sense. In his poetry act of opening his magic windows, he creates a profusion of metaphor he gets to show a magic world through of the writing, and, this diversity poetic is seen in all of his poem. This poetry text is extremately metaphoric. However, the metaphors that are in quintaneanos texts take not only to a metaphor that shows a surrealist message or daily image, but take to a single metaphor, a live metaphor that show a transposition of meanings.